Productivity of onion depending on the seeding fraction and feeding with water-soluble complex mineral fertilizers - T. E. Ivanova; E. V. Lekomtseva; T. N. Tutova; E. V. Sokolova (Овощи России, 2024)
The productivity of agricultural crops is determined by the choice of varieties, planting material, the optimal time of sowing and planting depending on the climatic conditions of the region, the use of organic and mineral fertilizers, and care methods. Planting material plays an important role in the growth and development of onions and the formation of yield. Onions are very demanding in terms of nutrition, this is due to the length of the growing season, growth rates and poorly developed root system. To obtain high and high-quality onion yields, it is necessary to use fertilizers in an accessible form. Water-soluble complex mineral fertilizers quickly and evenly penetrate deep into the soil. Fertilizers improve the growth and development of plants, regulating nutrition processes, increase the yield and quality of the resulting products. As a result of many years of research, it was found that optimizing the mineral nutrition of onions through the use of fertilizers in active form provides a significant increase in the yield of onions. A comparative assessment of the productivity of onions when grown from sets of different fractions using water-soluble complex mineral fertilizers in the conditions of the Udmurt Republic has been little studied.Materials and methods. The purpose of the research: to improve the technology of cultivating onions depending on the fraction of the set and fertilizing with water-soluble complex mineral fertilizers. In 2020–2021 On onions of the Stuttgarter Riesen variety, a two-factor experiment was carried out to study the effect of fertilizing with Aquarin and Rastvorin fertilizers when using different fractions of sets for planting. The studies were carried out using generally accepted methods.Results and its discussion. In the Udmurt Republic, the optimal for planting Stuttgarten Riesen onions is the medium and large fraction of the set, and the positive effect of water-soluble complex mineral fertilizers Aquarin and Rastvorin on the yield and its structure has been revealed. However, it is more economically profitable to use the fine fraction of sets when growing onions.